Differential estimation of carbon store contained in the coarse woody debris pool in the Belarussian near natural pine forests - Zhdanovich, Sergey A.; Pugachevskiy, Aleksandr V. (Journal of the Belarusian State University. Ecology, 2018)
Stores of carbon contained in the coarse woody debris (CWD) pool in the Belorussian near natural upland pine forests were determined. Average values of carbon store for different forests age groups were calculated: 6,5 ton С ha–1 in young-growth (aged 21–40), 9,0 ton С ha–1 in middle-aged (aged 41–60 лет), 10,1 ton С ha–1 in ripening, 9,1 ton С ha–1 in mature and 12,3 ton С ha–1 in old-growth forests. It’s equivalent to 15,6, 11,5, 11,5, 11,3 and 14,4 % of carbon store contained in the trunks of the living stands for above forest groups, respectively. The coefficients for conversion of CWD store into carbon mass for pine, spruce and birch coarse woody debris, including snags and logs of 1–5 decay stages were calculated.
Keywords: near natural pine forests; coarse woody debris; decay stages; carbon store